Fs-Laser-Induced Micro- and Nanostructures on Polycarbonate and Cellulose Acetate Butyrate for Cell Alignment - Lukas Wagner; Werner Baumgartner; Agnes Weth; Sebastian Lifka; Johannes Heitz (Applied Sciences, 2025)
Laser-generated structures have a huge potential to induce an alignment of biological cells, which may be important for various fields in medicine and biotechnology. We describe the formation of fs-laser-induced micro- and nanostructures for achieving the directed growth of Schwann cells, a type of glial cell that can support the regeneration of nerve pathways by guiding the neuronal axons in the direction of their alignment. Polymer surfaces, i.e., polycarbonate (PC) or cellulose acetate butyrate (CAB), were exposed to the beam of a 1040 nm Yb-based amplified fs-laser system with a pulse length of about 350 fs. With appropriate parameters, the laser exposure resulted in a surface topography with oriented micro-grooves, which, for PC, were covered with nano-ripples. Schwann cell growth on these substrates was inspected after 3 to 5 days of cultivation by means of scanning electron microscopy (SEM). We show that Schwann cells can grow in a certain direction, predetermined by micro-groove or nano-ripple orientation. In contrast, cells cultivated on randomly oriented nanofibers or unstructured surfaces show an omnidirectional growth behavior. This method may be used in the future to produce nerve conduits for the treatment of injuries to the peripheral nervous system.